The warden's daughter - Spinelli, Jerry (Alfred A. Knopf, 2017)
Living with her warden father in an apartment above a 1950s prison, Cammie O'Reilly struggles to come to terms with the loss of her mother, who died saving her from harm when she was a baby, and interacts with some of the reformed inmates.